Digital Media and the Transformation of Modern Cultural Narratives - Achilova , Shaxruza (INTERNATIONAL CONFERENCE ON SCIENCE, INNOVATION AND GLOBAL DEVELOPMENT, 2026)
Digital media has significantly changed how people communicate, interact and create culture. The shift from traditional forms like newspapers and television to online platforms has reshaped communication patterns, influenced cultural identities and changed social behavior. This study explores how digital media affects modern society and culture, including communication, globalization of culture, social interactions, political processes and cultural production. It also looks at both the positive and negative sides of this change, noting that while digital media increases participation and engagement, it also raises concerns such as misinformation, privacy issues and growing social divisions. Overall, the paper argues that digital media has a dual impact, promoting openness and access while also challenging traditional cultural system.